Family functioning and resilience in children in mainland China: life satisfaction as a mediator - Dou, Diya; Shek, Daniel T. L.; Tan, Lindan; Zhao, Li (Frontiers in Psychology, 2023)
Introduction: Grounded in the perspective of “Positive Youth Development” (PYD), resilience is an important developmental asset shaping human development. Although many studies have examined the impact of resilience on child developmental outcomes, relatively few studies have focused on the predictors of resilience, in particular familial antecedents of resilience in Chinese children and adolescents. In addition, the degree to which life satisfaction contributes to the mechanism by which family functioning impacts the development of children’s resilience over time needs to be clarified. Besides, there is a scarcity of studies that incorporate family functioning, resilience as well as life satisfaction in a single comprehensive investigation to analyze the mediating impact of life satisfaction on the linkage between family functioning and resilience under COVID-19. Methods: The study investigated the predictive role of family functioning on resilience as well as the mediating effect of life satisfaction within the context of COVID-19, using data gathered in two waves before the onset of the pandemic and after the resumption of school during the pandemic, with 6 months apart. We employed the 33-item “Chinese Family Assessment Instrument” to evaluate family functioning, the 7-item “Chinese Resilience Scale” to assess resilience, and the “Satisfaction with Life Scale” with 5 items to measure life satisfaction. Results: As per the responses of 4,783 students in Grades 4 through 7 recruited in Sichuan, China, family functioning significantly predicted resilience concurrently and longitudinally. After controlling for resilience scores in Wave 1, results demonstrated that family functioning examined in Wave 1 predicted an increase in resilience reported in Wave 2. In addition, family functioning significantly predicted life satisfaction, which also significantly predicted resilience. Multiple regression using PROCESS analyses indicated that life satisfaction mediated the predictive relationship between family functioning and child resilience. Discussion: The findings spotlight the significant involvement of family functioning as well as life satisfaction in shaping children’s resilience in the Chinese context. The study also supports the hypothesis that perceived satisfaction with life serves as a mediator between family functioning and child resilience, suggesting interventions and support should concentrate on the family level for enhancing resilience in children.